STUDI OTENTISITAS PEMAKNAAN HADITS TENTANG LARANGAN GRATIFIKASI - Ihsan Gasali (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2019)
Criminal decisions sourced from positive law which regulate the prohibition of gratification have been mainstream on our people’s ears, at least there are 30 types of corruption according to the laws of Indonesia, which are basically grouped into seven, are: 1) state financial losses, 2) bribe, 3) embezzlement of office funds, 4) racketeering, 5) manipulation, 6) conflict of interest in procurement, and 7) gratification. As we know that gratification (risywah) is like a virus that infects every people, especially the stakeholders in this country. At least it is caused bythe weakness of the moral foundation, dishonest, the amount of temptation in the form of material, moreover if it is related with a government system that still has a gap to do it. Related with the points above, this study tries to present the arguments (legal reasons and provisions) from Islamic law viewpoints, then analyzes about authenticity of the meaning of the hadith about the prohibition of gratification more deeply. The procedure for presenting this study begins with analyzing the sanad tree, which is the connection of the sanad and the symbol of the transmission that used by the narrator then the narrator's biography and comments on the sanad. Keywords: authenticity, hadith, narrator, sanad, gratification